Acquisition of Tigecycline Resistance by Carbapenem-Resistant Klebsiella pneumoniae Confers Collateral Hypersensitivity to Aminoglycosides - Chen, Hua-le; Jiang, Yan; Li, Mei-mei; Sun, Yao; Cao, Jian-ming; Zhou, Cui; Zhang, Xiao-xiao; Qu, Yue; Zhou, Tie-li (Frontiers in Microbiology, 2021)
Tigecycline is a last-resort antibiotic for infections caused by carbapenem-resistant Klebsiella pneumoniae (CRKP). This study aimed to broaden our understanding of the acquisition of collateral hypersensitivity by CRKP, as an evolutionary trade-off of developing resistance to tigecycline. Firstly, experimental induction of tigecycline resistance was conducted with tigecycline-sensitive CRKP clinical isolates. And then antimicrobial susceptibility testing, microbial fitness assessment, genotypic analysis and full-genome sequencing were carried out for these clinical isolates and their resistance-induced descendants. We found that tigecycline resistance was successfully induced after exposing CRKP clinical isolates to tigecycline at gradually increased concentrations, at a minor fitness cost of bacterial cells. Quantitative reverse transcription-polymerase chain reaction (RT-PCR) found higher expression of the efflux pump gene acrB (5.3-64.5-fold) and its regulatory gene ramA (7.4-65.8-fold) in resistance-induced strains compared to that in the tigecycline-sensitive clinical isolates. Stable hypersensitivities to aminoglycosides and other antibiotics were noticed in resistance-induced strains, showing significantly lowered MICs (X 4 - > 500 times). Full genome sequencing and plasmid analysis suggested the induced collateral hypersensitivity might be multifaceted, with the loss of an antimicrobial resistance (AMR) plasmid being a possible major player. This study rationalized the sequential combination of tigecycline with aminoglycosides for the treatment of CRKP infections.